Influence of previous aspirin treatment and smoking on the electrocardiographic manifestations of injury in acute myocardial infarction. Issue 1 (1st July 2000) - Kennon, S; Barakat, K; Suliman, A; MacCallum, P K; Ranjadayalan, K; Wilkinson, P; Timmis, A D
Abstract : OBJECTIVE: To examine demographic and clinical characteristics of patients with acute myocardial infarction in order to identify factors affecting the electrocardiographic evolution of injury. METHODS: Prospective cohort study of 1399 consecutive patients with a first myocardial infarction. Baseline clinical data associated with ST elevation and Q wave development were identified and 12 month survival was estimated. RESULTS: Smoking had complex effects on the evolution of injury, increasing the odds of ST elevation (odds ratio (OR) 1.61; 95% confidence interval (CI) 1.08 to 2.36), but reducing the odds of Q wave development (OR 0.69, 95% CI 0.49 to 0.96). The effects of previous aspirin treatment were more consistent with reductions in the odds of ST elevation (OR 0.57, 95% CI 0.35 to 0.94) and Q wave development (OR 0.53, 95% CI 0.34 to 0.84). ST elevation and Q wave development were both associated with an adverse prognosis, with estimated 12 month survival rates of 80.6% (95% CI 78.2% to 83.1%) and 80.0% (95% CI 77.5% to 82.5%), respectively, compared with 86.5% (95% CI 81.2% to 91.9%) and 89.9% (95% CI 86.2% to 93.7%) for patients without these ECG changes. CONCLUSIONS: The thrombogenicity of the blood may be a major determinant of infarct severity. Smoking increases thrombogenicity and the likelihood of ST elevation, but because coronary occlusion is relatively more thrombotic in smokers, responses to both endogenous and exogenous thrombolysis are better, reducing the risk of Q wave development. Previous aspirin treatment reduces thrombogenicity, protecting against ST elevation and Q wave development.